Emergencia de Angiostrongylus cantonensis en el caracol gigante africano - Hernández Ferreras, Kiria; Castillo Vila, Julio Alberto; Varona Green, Cecilia Margarita (Revista Cubana de Investigaciones Biomédicas, 2020)
no procede